Bimetallic Cobalt–Copper Nanoparticle-Decorated Hollow Carbon Nanofibers for Efficient CO2 Electroreduction - He, Congyi; Wang, Siyu; Jiang, Xingxing; Hu, Qi; Yang, Hengpan; He, Chuanxin (Frontiers in Chemistry, 2022)
Bimetallic materials are one of the most promising catalysts for electrochemical reduction of CO2, but there are still many challenges to be overcame on the route to industrialization. Herein, a series of carbon nanofibers supported bimetallic cobalt-copper catalysts (CoxCuy/CFs) are designed and constructed through electrospinning technique and a subsequent pyrolysis procedure. Small-sized Co-Cu nanoparticles are homogenously distributed on the porous carbon nanofibers, which can significantly improve the utilization rate of metal sites and greatly reduce the loading amount of metals. Moreover, different product distribution and catalytic performance can be obtained in CO2 reduction via adjusting the metal proportion CoxCuy/CFs. Especially, Co3Cu/CFs can bring forth a 97% total faradaic efficiency (FE) of CO (68%) and HCOOH (29%) at –0.8 VRHE cathode potential in 0.5 M KHCO3 electrolyte. Furthermore, the hierarchical pores can firmly confine the small Co-Cu nanoparticles and keep them from easy agglomeration during electrolysis, eventually leading to the 60-hour stability for Co3Cu/CFs in CO2 electroreduction. This study might provide a facile and economic method to fabricate efficient bimetallic catalysts for CO2 electroreduction and other electrocatalysis application.